1957
DOI: 10.1042/bj0670487
|View full text |Cite
|
Sign up to set email alerts
|

The oxidative activity of particulate fractions from mosquitoes

Abstract: Watanabe & Williams (1951, 1953) were the first to perform biochemical studies on insect sarcosomes. Evidence was provided for the operation of the citric acid cycle in sarcosomes of the housefly

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

1961
1961
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…This strongly indicates that lipids are not suitable substrates to support respiration in A . aegypti flight muscle, as previously suggested [ 47 ]. CS activities were high and compatible with values obtained for other insects [ 59 ].…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…This strongly indicates that lipids are not suitable substrates to support respiration in A . aegypti flight muscle, as previously suggested [ 47 ]. CS activities were high and compatible with values obtained for other insects [ 59 ].…”
Section: Resultssupporting
confidence: 75%
“…Previous investigations of mitochondrial physiology in A . aegypti flight muscle revealed that both respiration and ADP phosphorylation were induced by tricarboxylic acid cycle intermediates, in DDT-sensitive reactions [ 47 , 48 ]. Our group has shown that in females of A .…”
Section: Introductionmentioning
confidence: 99%
“…With serum albumin in the reaction medium P:O ratios were obtained approaching those found with mammalian preparations (Sacktor & Cochran, 1958;Cochran & King, 1960). Further, sarcosomes have been isolated from different insect species that exhibit respiratory control in the absence of ADP (Gonda et al 1957;Klingenberg & Bucher, -1959;Gregg et al 1960). Finally, it was shown that high P:O ratios could be obtained without addition of serum albumin and that pyruvate could be oxidized even more rapidly than oa-glycerophosphate (Gregg et al 1960).…”
Section: Discussionmentioning
confidence: 99%
“…Originally, no phosphorylation coupled to the oxidation of foodstuffs was found in sarcosomes from insect sources (Sacktor, 1953). But after Lewis & Slater (1953) had demonstrated oxidative phosphorylation in sarcosomes from the blowfly, their results were confirmed for sarcosomes from the locust (Rees, 1954), housefly (Sacktor, 1954), mosquito (Gonda et al 1957), wax-moth larva (Wojtczak & Wojtczak, 1959), cockroach (Cochran & King, 1960) and blowfly larva (Newburgh, Potter & Cheldelin, 1960). In most cases the addition of serum albumin to the reaction medium had a pronounced stimulatory effect on phosphate esterification.…”
mentioning
confidence: 91%
See 1 more Smart Citation